2020
DOI: 10.1053/j.jrn.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Prebiotic, Probiotic, and Synbiotic Supplementation in Modulating Gut-Derived Circulatory Particles Associated With Cardiovascular Disease in Individuals Receiving Dialysis: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: DSM and JOB developed the review topic. DSM and AWJ designed and developed the topic protocol. DSM and AWJ coordinated the review process. DSM and AWJ conducted the trial searches, screened the search results, assessed the trials for quality, extracted the data and analysed the data. DSM, AWJ, JOB and NCB prepared the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
(207 reference statements)
5
9
0
Order By: Relevance
“…This meta-analysis found reductions in p-CS and endotoxin levels after supplementation. This is consistent with the conclusion of a previous review by March et al, which included trials with patients receiving hemodialysis or peritoneal dialysis [13]. However, in contrast to our findings, they reported that probiotic, prebiotic, and synbiotic supplementation had a remarkable effect on decreasing IS levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This meta-analysis found reductions in p-CS and endotoxin levels after supplementation. This is consistent with the conclusion of a previous review by March et al, which included trials with patients receiving hemodialysis or peritoneal dialysis [13]. However, in contrast to our findings, they reported that probiotic, prebiotic, and synbiotic supplementation had a remarkable effect on decreasing IS levels.…”
Section: Discussionsupporting
confidence: 93%
“…A meta-analysis that focused on their effects in chronic kidney disease (CKD) patients with or without dialysis has been reported [ 12 ]. Recently, March et al demonstrated their efficacy on gut-derived toxic metabolites, lipid profiles, and clinical outcomes in patients receiving hemodialysis or peritoneal dialysis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study observed no effect on echocardiographic parameters, blood pressure, and lipid profile. This is in agreement with recent meta-analyses that highlighted that supplementation had no effect on serum lipids [9,27]. To our knowledge, no prior intervention study has reported data on GLS, LVMI, and blood pressure after synbiotic supplementation.…”
Section: Discussionsupporting
confidence: 93%
“…L. rhamnosus GR-1 and L. plantarum 299v reduce the risk of myocardial infarction, improve ventricular function, and reduce the infarct size by decreasing the levels of leptin in rats (316,317). Probiotics also decreased the levels of toxic circulating metabolites (indoxylsulfate and p-cresyl sulfate) associated with cardiovascular diseases and reduced mortality in patients undergoing dialysis (349). Probiotics exert beneficial effects on cardiovascular diseases through different mechanisms of action (i.e., improving the ratio of low-density and high-density lipids, lowering cholesterol levels, improving endothelial function, and regulating the immune cells) (Table 5).…”
Section: Probiotics Therapies In Non-infectious Disordersmentioning
confidence: 99%